Avaliação de políticas industriais de formação de polos e zonas francas sob o paradigma de cadeias de suprimento - Armando Araujo de Souza Junior (2014)
Companies have faced a complex and highly competitive environment, with increasingly demanding consumer, cycles of smaller products, and intense technological evolution. Competition no longer occurs between isolated organizations, but it does between supply chains. Integrated management of the supply chains becomes the difference of the new form of competition. In this context, Supply Chain Management (SCM) consists in the management of existing relationships among companies trough links of different processes along the chain that produces value in the form of products and services to the customers. The main goal of this thesis was to clarify the relationship with local suppliers, as well as qualify the barriers to attract strategic suppliers to Industrial Poles/Zones far from the consumer centers and suppliers of inputs. Thus, this research assessed the regional development model of Industrial Poles/Free Zones under the paradigm of supply chains. So, the option in this study was using quantitative and qualitative research, through a multiple case study, taking as unit of analysis the relationships of five focus companies of different nationalities, such as: America, Brazilian, Chinese, Korean and Japanese. It was possible to develop this sense of thought because of the local first tier suppliers of electronics subsector of electronics subsector of the Industrial Pole of Manaus (IPM). Data were collected through managers of supply of five surveyed focal companies, as well as through a survey with the managers of supplies from local suppliers. In data analysis assumptions of Network Theory, exploratory factor analysis to reduce the number of variables, descriptive statistical techniques content analysis was used. The local supply chain shows low density into the relationships and concentrates few strategic suppliers for the global electronics industry. Local suppliers provide input with low added value, which implies that can be replaced at any time. Therefore, the local supply chains is not integrated, and there is no collaboration/cooperation in the relationships studied. The redirection to the basic Productive Process for logical development of the supply chain, economies of scale bureaucracy, lack of skilled labor, low density of Research & Development, and poor logistics infrastructure were identified as barriers that hamper the attraction of strategic suppliers to local supply chain.